High-Throughput, Temporal and Dose Dependent, Effect of Vitamins and Minerals on Chondrogenesis - Dennis, James E.; Splawn, Taylor; Kean, Thomas J. (Frontiers in Cell and Developmental Biology, 2020)
Tissue engineered hyaline cartilage is plagued by poor mechanical properties largely due to inadequate type II collagen expression. Of note, commonly used defined chondrogenic media lack 14 vitamins and minerals, some of which are implicated in chondrogenesis. Type II collagen promoter-driven Gaussia luciferase was transfected into ATDC5 cells to create a chondrogenic cell with a secreted-reporter. The reporter cells were used in an aggregate-based chondrogenic culture model to develop a high-throughput analytic platform. This high-throughput platform was used to assess the effect of vitamins and minerals, alone and in combination with TGFβ1, on COL2A1 promoter-driven expression. Significant combinatorial effects between vitamins, minerals and TGFβ1 in terms of COL2A1 promoter-driven expression and metabolism were discovered. An ′optimal′ continual supplement of copper and vitamin K in the presence of TGFβ1 gave a 2.5-fold increase in COL2A1 promoter-driven expression over TGFβ1 supplemented media alone in ATDC5 cells.